2002
DOI: 10.1128/mcb.22.7.2375-2387.2002
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2A Forms a Molecular Complex with Shc and Regulates Shc Tyrosine Phosphorylation and Downstream Mitogenic Signaling

Abstract: Protein phosphatase 2A (PP2A) is a multimeric serine/threonine phosphatase that carries out multiple functions. Although numerous observations suggest that PP2A plays a major role in downregulation of the mitogen-activated protein (MAP) kinase pathway, the precise mechanisms are unknown. To clarify the role of PP2A in growth factor (insulin, epidermal growth factor [EGF], and insulin-like growth factor 1 [IGF-1]) stimulation of the Ras/MAP kinase pathway, simian virus 40 small t antigen was expressed in Rat-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
82
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 64 publications
(118 reference statements)
12
82
1
Order By: Relevance
“…Thorough literature analysis revealed that the members of this gene cluster are functionally inter-related. First, it has been shown that protein phosphatase 2A (PP2A) is involved in the insulin/IGF-1 signal-transduction pathway (Ugi et al 2002). The presence of IGF-2 and PP2A in the same SP group is consistent with the observation that PP2A participates in IGF-2 signaling.…”
Section: Verification Of Functional Relationships Using Shortest-pathsupporting
confidence: 72%
See 1 more Smart Citation
“…Thorough literature analysis revealed that the members of this gene cluster are functionally inter-related. First, it has been shown that protein phosphatase 2A (PP2A) is involved in the insulin/IGF-1 signal-transduction pathway (Ugi et al 2002). The presence of IGF-2 and PP2A in the same SP group is consistent with the observation that PP2A participates in IGF-2 signaling.…”
Section: Verification Of Functional Relationships Using Shortest-pathsupporting
confidence: 72%
“…Physical interactions between members of this group have also been characterized. Shc is known to interact physically with PP2A (Ugi et al 2002) and cadherin (Xu et al 1997). Cadherins can also interact with a receptor-type protein tyrosine phosphatase (Brady-Kalnay et al 1998), in agreement with the presence of both cadherin and receptor-type protein tyrosine phosphatase in the IGF-2 group (Fig.…”
Section: Genome Research 2711supporting
confidence: 63%
“…CREB is involved in neoplastic transformation and, being activated via PKA by cAMP, is also involved in the growth of normal thyroid follicular cells (38)(39)(40)(41). Our data show that CD44-ICD binds CREB and increases pS133 CREB levels.…”
Section: Discussionmentioning
confidence: 53%
“…PP2A is a family of Ser/Thr protein phosphatases that are the major phosphatases of Akt/PKB, p70S6 kinase, as well as ERK1/2 [26,27]. Hence, a potential cellular mechanism to explain the results described above is an enhanced rate of dephosphorylation of these kinases by PP2A.…”
Section: Increased Pp2a Content and Activity Or Increased Expressionmentioning
confidence: 97%